Evaluation of a Platinum–Acridine Anticancer Agent and Its Liposomal Formulation in an in vivo Model of Lung Adenocarcinoma. (22nd October 2020) - Ding, Song; Hackett, Christopher L.; Liu, Fang; Hackett, Ryan G.; Bierbach, Ulrich
Abstract: Liposomal formulations have been developed for a highly cytotoxic platinum–acridine agent, [PtCl(pn)(C18 H21 N4 )](NO3 )2 (PA, pn=propane‐1, 3‐diamine), and fully characterized. Nanoliposomes consisting of hydrogenated soybean phosphatidylcholine (HSPC), 1, 2‐dihexadecanoyl‐sn‐glycero‐3‐phospho‐(1'‐rac‐glycerol) (DPPG), and polyethylene glycol‐2000‐distearoylphosphatidylethanolamine (DSPE‐mPEG2k ) were able to stably encapsulate PA at payload‐to‐lipid ratios of 2–20 %. The fusogenic properties of the liposomes promote efficient cellular uptake of PA across the plasma membrane, which results in vesicular transport of payload to the nucleus in cultured lung cancer cells. Unencapsulated PA and one of the newly designed liposomal formulations show promising tumor growth inhibition in tumor xenografts derived from A549 lung adenocarcinoma cells of 76 % and 72 %, respectively. Cisplatin showed no significant efficacy at a 10‐fold higher dose. These findings underscore the utility of platinum‐acridine agents for treating aggressive, chemoresistant forms of cancer and validate nanoliposomes as a biocompatible, expandable platform for their intravenous delivery and other potential routes of administration. Abstract : PA payloads : Promising inhibition of lung tumor growth in mice is observed for a cytotoxic platinum‐acridine hybrid agent (PA) when injected directly or as a hydrophilic payload in nanoliposomes. PA, due to its potency and unique spectrum of activity, promises utility in treating aggressive solid tumors resistant to cisplatin and other conventional chemotherapies.